The use of mobile application: why play is important in teaching elementary mathematics? - Alkhaldi, Ibrahim; Talib, Othman; Kamarudin, Nurzatulshima; Ab. Jalil, Habibah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The used of mobile applications or apps by the actual digital users as an everyday object are becoming the new frontier of software development and this could be adopted in educational environment in order to improve teaching and learning. The uses of technology in teaching children has recommended in connection with the development level of the children who are generally believed to have low memory capacity, less attention and always want play. Hence, this article was aimed at reviewing relevant literature on the use of mobile application and the need for the integration of game activities in the mobile application especially for teaching mathematics at elementary schools. This paper elaborates on the systematic literature review process done on the 28 selected journal articles and papers on mobile application topic. The analysis reveals that, while different mobile application are developed in various field, most of them share similar themes in enhancing students’ performance. However, there is no enough application integrating game activities to help students learn with fun especially in mathematics at elementary level. These findings act as a heuristic device to propose a development of a fund driven mobile application for teaching mathematics at elementary level. It is hoped that that by integrating games activities, sound, images and pictures in developing mobile application for teaching mathematics at elementary level pupil’s attention could be attracted and mathematics teaching and learning would become funny and easily understand by the students. This is in order to satisfy the curiosity nature of children to play as playing have been considered important part of students learning. The study further suggested by combining multimedia learning theory, game-based learning theory and cognitive development theory of learning can serve as a theoretical bases for the proposed application. Moreover, while integrating play as an element of fun in mobile learning careful consideration should be given to the types of sound, pictures and or images used as well as the cultural and psychological issues to the child and the environment.